2022
DOI: 10.3390/molecules27238359
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Luminescent Properties of Novel Organotin Complexes with Chelating Antioxidant Ligand

Abstract: A novel polydentate chelating antioxidant ligand and series of organotin complexes on its base were synthesized and characterized by NMR 1H, 13C, 119Sn, IR spectroscopy, X-ray, and elemental analysis. Their antioxidant activity was evaluated in DPPH and NBT-tests, and as lipoxygenase inhibitory activity. It was shown that ligand alone is a radical scavenger, while introducing tin in the structure of the compound significantly decreases its activity. For the ligand alone the ability to strongly suppress the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…15 This is followed by the oxidation of xanthine to uric acid following a superoxide radical (O 2 ˙ − ) mechanism. 16 Inspired by this reaction in nature, we carried out a similar oxidation reaction of hypoxanthine using 1 . The oxidation of hypoxanthine to xanthine was achieved by treating hypoxanthine with 1 mmol TBHP as the oxidant and 5 mol% of 1 taking in CH 3 CN : H 2 O (1 : 1) mixture at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 This is followed by the oxidation of xanthine to uric acid following a superoxide radical (O 2 ˙ − ) mechanism. 16 Inspired by this reaction in nature, we carried out a similar oxidation reaction of hypoxanthine using 1 . The oxidation of hypoxanthine to xanthine was achieved by treating hypoxanthine with 1 mmol TBHP as the oxidant and 5 mol% of 1 taking in CH 3 CN : H 2 O (1 : 1) mixture at room temperature.…”
mentioning
confidence: 99%
“…Xanthine oxidase is known to catalyze xanthine to uric acid, yielding a superoxide radical anion (ROS, O 2 ˙ − ). 16 Further, ROS production can be spectroscopically monitored by the reduction of nitro-blue tetrzolium (NBT). 17 To a stirred DMSO solution of NBT, compound 1 and TBHP were added, and absorption spectra were recorded over a period of 40 min (ESI, Fig.…”
mentioning
confidence: 99%
“…This provides an opportunity to combine the quinoline and 2,6-DTBP fragments into a quaternary ammonium molecule with the goal of unlocking a synergistic effect toward enhanced On the other hand, the research on 2,6-tert-butyl phenol (2,6-DTBP) derivatives is limited and is mainly focused on its antioxidative properties. For example, in a study by Milaeva et al, the 2,6-DTBP fragment was included in a series of organotin complexes showing antioxidative, luminescent, and cytotoxic properties [26]. Moreover, Berberova et al demonstrated the antioxidative and cytotoxic activity of aromatic oligosulfides bearing the same fragment [27].…”
Section: Introductionmentioning
confidence: 99%